2004
DOI: 10.1086/380128
|View full text |Cite
|
Sign up to set email alerts
|

Risk Behavior for Transmission of Human Immunodeficiency Virus (HIV) among HIV‐Seropositive Individuals in an Urban Setting

Abstract: We conducted interviews with 256 human immunodeficiency virus (HIV)-infected patients who attended an HIV clinic in New York City to assess ongoing risk behaviors for HIV transmission. After learning that the result of an HIV test was positive, 106 subjects (41%) had unprotected sex, 63 (25%) had a new sexually transmitted disease diagnosis, and 38 (15%) used injection drugs. Unprotected sex was reported by 50% of women, 29% of heterosexual men (P=.006, compared with women), and 42% of men who have sex with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
51
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 24 publications
3
51
0
2
Order By: Relevance
“…Probability samples are rare. More often studies have relied upon convenience samples of volunteers recruited from clinic or service settings [9][10][11] or from venues such as bars where sexually active, HIV-positive persons were expected to be found. 6,12 Studies have been cross-sectional or covered short time spans.…”
Section: Introductionmentioning
confidence: 99%
“…Probability samples are rare. More often studies have relied upon convenience samples of volunteers recruited from clinic or service settings [9][10][11] or from venues such as bars where sexually active, HIV-positive persons were expected to be found. 6,12 Studies have been cross-sectional or covered short time spans.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 These strategies seem promising in altering the HIV epidemic, but are under debate due to some observations of high-risk populations having low levels of risk perception, 29 and HIV-positive patients increasing risky sexual behaviors in the HAART era. [30][31][32][33] Previous studies have shown that under regular medical care, HIV-positive patients decrease their sexual risk behaviors by 30-55%, 30,33 especially in the initial years following the 158 CHENG ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 In New York, people who had known their HIV-infected status for > 5 years were more prone to sexual risk behaviors. 32 In Amsterdam, HIV-positive MSM had 61% of increase of unprotected anal sex after 4 years of seroconversion. 30 In Northern Taiwan, Chen and colleagues 20 demonstrated that HIV status awareness for > 11 years was accompanied by a 2-fold higher likelihood of practicing unprotected sexual behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…A study among 919 HIV-infected patients who attended the STI clinic of Taipei City, Taiwan, in 2004 found that 476 (52%) had a new STI diagnosis after HIV diagnosis [6]. Likewise, in a study that assessed ongoing risk behaviors for HIV transmission among 256 patients attending an HIV clinic in New York City [7], 63 patients (25%) had a new STI after HIV diagnosis. It is unclear whether the widespread access to antiretroviral therapy has changed the sexual behavior and therefore risk of acquisition of HIV in HIV-infected patients undergoing HIV care.…”
Section: Introductionmentioning
confidence: 99%